The Hubble Space Telescope and the high redshift universe 37th Herstmonceux Conference, Cambridge, United Kingdom, July 1-5, 1996 (World Scientific Publishing Co. Pte Ltd, 1997)
"Since the successful refurbishment mission, the Hubble Space Telescope has made dramatic and exciting progress in unravelling the nature of sources at high redshift. The upcoming installation of the next generation of instruments will give further impetus to the field, particularly in the infrared spectral region. The proceedings of this landmark meeting review the results of the first three years of post-repair data, including the deepest astronomical images ever obtained: the Hubble Deep Field. This was the first presentation of these exciting results at a major international conference. The interface between HST and ground-based facilities and planned programmes with forthcoming HST instruments are also extensively discussed."--Publisher's website